Glycemic Control in Patients with Type 2 Diabetes Mellitus: Descriptive Survey in Makassar City Hospitals - Yusran Haskas; Suarnianti Suarnianti; Indah Restika (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: This study aims to determine the frequency distribution based on the respondent's glycemic control in the hospitals in Makassar City Methdos: This research is a non-experimental quantitative research using descriptive method. This research was conducted in hospitals in Makassar City, South Sulawesi (RSUD Kota Makassar, Bhayangkara Hospital Makassar, Pelamonia Hospital Makassar, Labuang Baji Hospital, RSUD Haji Makassar, and Ibnu Sina Hospital Makassar). The total of samples in this study amounted to 291 patients with diabetes mellitus using purposive sampling. Results: Based on the results of the our study, it was found that there were 161 (55.3%) people with diabetes mellitus with less glycemic control and 130 (44.7%) people with diabetes mellitus with good glycemic control. Conclusions: In the management of diabetes management with monitoring blood sugar levels is very important. Thus, good glycemic control will be declined diabetes complications. Consequently, it is highly recommended for people with diabetes mellitus to reduce the complications of Type 2 DM by complying with glycemic control.